Removal of Heavy Metals by a Membrane Bioreactor Combined with Activated Carbon - Calik, Savas; Sozudogru, Onur; Massara, Theoni Maria; Yilmaz, Alper Erdem; Bakirdere, Sezgin; Katsou, Evina; Komesli, Okan Tarik (TAYLOR & FRANCIS INC, 2020)
The removal of nickel, lead, arsenic, and zinc was investigated by a lab-scale submerged membrane bioreactor (MBR) combined with granular activated carbon (GAC). Membrane fluxes of 16 L m(-2)h(-1), 20 L m(-2)h(-1), and 24 L m(-2)h(-1)with corresponding hydraulic retention times (HRTs) of 12.8 h, 10.4 h, and 9.2 h were applied as variables to examine their influence upon the removal efficiency. Synthetically prepared wastewater was pretreated in the MBR and GAC adsorption was employed as the post-treatment. Under the lowest applied flux value or, equivalently, the highest HRT applied, chemical oxygen demand (COD), ammonium (NH4-N) and phosphate (PO4-P) removals were found to be the highest (96.8%, 98.9% and 46%, respectively) for the MBR effluent. These results may be considered to be the result of alleviated membrane fouling and greater biomass growth. The highest heavy metal removal efficiency after the first treatment stage (i.e. the MBR effluent) was obtained at the lowest flux value of 16 L m(-2)h(-1). Ni, Pb, Zn, and As removals were measured to be equal to 96.9%, 98.3%, 98% and 8.5%, respectively. More important, the heavy metal concentrations were below the limit of detection after the GAC post-treatment; over 99% removal was achieved for all heavy metals. The adsorption of heavy metal ions onto the GAC may minimize biomass exposure to their toxicity, thereby creating the conditions for further improved MBR-GAC system performance. Coupling MBR technology with GAC adsorption seems a promising option for the effective treatment of wastewater containing heavy metals.
Keywords: Adsorption; flux; granular activated carbon; heavy metal removal; membrane bioreactor; WASTE-WATER TREATMENT; HYDRAULIC RETENTION TIME; AQUEOUS-SOLUTIONS; SOLID-WASTE; INDUSTRIAL; IONS; REGENERATION; BIOSORPTION; WASTEWATERS; Chemistry